2017
DOI: 10.1103/physreva.95.053636
|View full text |Cite
|
Sign up to set email alerts
|

Dual cascade and dissipation mechanisms in helical quantum turbulence

Abstract: While in classical turbulence helicity depletes nonlinearity and can alter the evolution of turbulent flows, in quantum turbulence its role is not fully understood. We present numerical simulations of the free decay of a helical quantum turbulent flow using the Gross-Pitaevskii equation at high spatial resolution. The evolution has remarkable similarities with classical flows, which go as far as displaying a dual transfer of incompressible kinetic energy and helicity to small scales. Spatio-temporal analysis i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 41 publications
12
59
0
Order By: Relevance
“…This difference might be due to the fact that the present simulations are freely decaying, and have no force acting to sustain turbulence. The existence of two simultaneous inertial ranges separated by a bottleneck was also observed before in high resolution simulations using dif-ferent initial conditions [28], but was not visible in the N = 512 DNS of a TG flow in [24] possibly as a result of the limited spatial resolution in that study. To further illustrate these ranges, and the scale separation involved, in Fig.…”
Section: A High Resolution Gpe Runs At T =supporting
confidence: 65%
“…This difference might be due to the fact that the present simulations are freely decaying, and have no force acting to sustain turbulence. The existence of two simultaneous inertial ranges separated by a bottleneck was also observed before in high resolution simulations using dif-ferent initial conditions [28], but was not visible in the N = 512 DNS of a TG flow in [24] possibly as a result of the limited spatial resolution in that study. To further illustrate these ranges, and the scale separation involved, in Fig.…”
Section: A High Resolution Gpe Runs At T =supporting
confidence: 65%
“…Such a study has been carried out in the literature using the local formulation of the GP equation (Eq. 10) [29,47], that we repeat here for the nonlocal version. Decomposing the conserved total energy as the sum of various components, we identify the part associated to kinetic energy as being the average (over space and time, the time integration starting at t rec until the end of the simulation) of the norm square of the vector √ ρv, a vector field being itself decomposed into a divergence-free part (i.e.…”
Section: Numerical Investigation Of Reconnection Of a Set Of Initmentioning
confidence: 99%
“…At zero or near zero temperatures the GPE, for which quantized vortices are exact solutions which can reconnect with no extra ad-hoc assumptions, is a very succesful model for BECs [19]. Moreover, a hydrodynamic analogy can be easily obtained from the GPE by means of the Madelung transformation, and it has been shown that at the larger scales its turbulent solutions match those of classical turbulence [20,21]. There are various ways of generalizing the GPE for studying finite-temperature effects [22].…”
Section: Introductionmentioning
confidence: 99%
“…The usual picture of quantum turbulence (see, for example, [1]) goes by the following: while at the larger scales the nonlinear energy transfer in quantum flows is mediated by the interaction between vortices and reconnection processes [45], and the turbulent flow resembles that of a classical fluid, at scales smaller than the mean intervortex length Kelvin waves are believed to be the ones responsible for the energy transfer, thus generating Kelvin wave turbulence [13,44,[46][47][48]. Nonlinear interaction of Kelvin waves leads to the creation of phonons [49], which are finally responsible for the depletion of incompressible kinetic energy in quantum turbulence [21,50]. Additionally, recently it was shown that at zero temperature helical quantum turbulence (i.e., for flows with non-zero largescale helicity) develops a dual cascade of energy and of helicity reminiscent of the dual cascade observed in classical helical flows, and that the emission of phonons also result in the depletion of helicity [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation